Discrete-Event Simulation of Quantum Walks - Willsch, Madita; Willsch, Dennis; Michielsen, Kristel; De Raedt, Hans (Frontiers in Physics, 2020)
We use discrete-event simulation on a digital computer to study two different models of experimentally realizable quantum walks. The simulation models comply with Einstein locality, are as ``realistic'' as the one of the simple random walk in that the particles follow well-defined trajectories, are void of concepts such as particle-wave duality and wave-function collapse, and reproduce the quantum-theoretical results by means of a cause-and-effect, event-by-event process.